Corporate culture and stock returns: evidence from Indian companies. Issue 4 (30th August 2019) - Aziz, Tariq; Ansari, Valeed Ahmad; Alam, Mahfooz
Abstract : Purpose: The purpose of this paper is to investigate the stock market performance of companies featured in the survey "Best Companies to Work For" as a proxy for corporate culture. Design/methodology/approach: The authors employed the portfolio formation and event study methods from finance to examine the linkage between corporate culture and future stocks returns. The lists of India's best place to work for by Great Place to Work® Institute and Business Today ( BT ), India's leading business magazine, form the primary surrogate for a great corporate culture. The authors compared the stock market performance of the culture portfolio vis-à-vis market index, in addition to using Carhart's (1997) four-factor model. Findings: A portfolio of Indian firms that featured in the "Best Companies to Work For" by Great Place to Work© Institute and BT magazine provides a higher return than the market index Sensex both on an ordinary return and on a risk-adjusted basis. The four-factor α s of the value-weighted culture portfolios are significant, implying that these portfolios have provided abnormal returns during the sample period. Moreover, the findings suggest a positive drift in the abnormal returns after inclusion in the "Best Companies to Work For" list. Research limitations/implications: The results are largely in conformity with the prediction of the theory that states that corporate culture is an economic asset for a firm that increases its value. Practical implications: From an investor's point of view, the study indicates that investment in "Best Companies to Work For" is a better alternative than passive index investing. Originality/value: This study fills the empirical void in the relationship between corporate culture and stock market performance in the Indian context.